PENGARUH PENAMBAHAN LIMBAH KARET BAN LUAR PADA LAPIS TIPIS ASPAL PASIR (LATASIR) TERHADAP KARAKTERISTIK MARSHALL - Fakhrul Rozi Yamali; Fakhrul Rozi Yamali (Jurnal Civronlit Unbari, 2018)
The mixture of asphalt sand or often called as LATASIR (a thin Layer of asphalt Sand) is often used on the streets as light as local roads or road environment, in order to restrain the rate of water so as not to enter into pores in it. This mixture consists only of fine aggregate or sand or a mixture of both, so of coarse aggregate is not found in its alloy, so have the resilience of the Groove (rutting) are low and cannot be used on roads with heavy traffic or the area slopes. To improve the quality of asphalt mixture Latasir then do the addition of waste tire rubber out of the motor. This research was conducted with the marshall test asphalt plan levels, with 7%, 8%, 9%, 10% and 11% in advance. After obtained the value levels of Optimum Asphalt (KAO), then do the test with the addition of marshall rubber tyres outside the motor of 1%, 2%, 3%, 4% and 5% against weight. The research results obtained a value of 9.8%, KAO then conducted testing of marshall by using a variation of the rubber tyres outside the motor changes characteristic of Marshall, the degree of suppleness and durability is better, but there is a cavity the air that many great VIM or value, so that the value of the VFA became small. From all levels of rubber in asphalt has a great degree of flexibility in rubber 3%, but that filled the whole terms of the 2010 revision 3 technical specifications on levels of 1.5% rubber.Keywords: Latasir Mixture, KAO, Waste Rubber Tyres Outside Motor, Marshall